A Water Management Solution of the Water Reservoir of Nýrsko - Lacina, Martin (Vysoké učení technické v Brně,Fakulta stavební, 2024)
This article focuses on a water management solution of the storage function of the Nýrsko reservoir for compensatory runoff control for the Homolka water treatment plant in Pilsen. The aim is to develop a water management solution for the Nýrsko reservoir that simulates the compensatory runoff management and estimates the inflow from the interbasin using a hydrological model for current climate data and for the climate change scenario data in the periods between 2041 to 2060 and 2061 to 2080.
Keywords: Water reservoir Nýrsko; storage function; water management solutions; GR4J; CemaNeige